Dynamic Relationship between the Dow Jones Industrial Average, Nikkei 225, Hang Seng Index and the Jakarta Composite Index - Didik Gunawan (Institute of Computer Science (IOCS), 2022)
This aims of study to determine the short-term and long-term effects of the Dow Jones Industrial Average, Nikkei 225, Hang Seng Index and the Jakarta Composite Index (JKSE). The data analysis technique uses the Vector Error Correction Model (VECM). The results showed that in the long term the Dow Jones Industrial Average variable had a significant negative effect on the JKSE while in the short term the Dow Jones Industrial Average had no effect on the JKSE, in the long term the Nikkei 225 variable had a positive and significant effect on the JKSE, while in the short term the Nikkei 225 did not. has an influence on the JKSE, in the long term the Hang Seng variable has a negative and significant effect on the JKSE, while in the short term the Hang Seng Index variable has no effect on the JKSE. In the short term the Dow Jones Industrial Average variable has a relationship with the Nikkei 225 variable, and the Nikkei 225 variable has no significant effect on the Hang Seng variable, while in the short term the Dow Jones Industrial Average variable has no relationship with the Hang Seng variable. This study proves that in the long term the stock index of a country with a strong economy will affect the stock index of other countries, the negative impact of this finding is that the economy of a country is easily affected by economic crises that occur in other countries.